Male crime victims: the social and personal construction of meaning in response to traumatogenic events - Eagle, Gillian (My University, 2014)
The study was directed at exploring the social and personal construction of meaning of male victims of violent crime. Three inter-related goals were identified: the extension of the nascent narrative/thematic tradition of analysis in the traumatic stress field; the deepening of appreciation of the experience of criminal victimization; and the exploration o f the role of social construction in the cognitive schematic adjustment of victims. In this instance the examination of the role of social construction was focussed centrally on the juxtaposition of the subject roles associated with masculinity and victimization. On the basis of both clinical observation and theory, it was postulated that aspects of masculine identification would create difficulties for men attempting to adjust to involuntary exposure to a context in which they were clearly victimized. The thesis provides comprehensive coverage of theory straddling cognitive adjustment to psychological trauma, mainstream and critical social psychological theory on victimization, developmental and descriptive dimensions of theory on masculinity and a range of literature on criminal victimization. The theoretical conceptualization underpinning the study offers a unique integration of this body of knowledge. In order to investigate the research question, ten adult, white, English speaking,South African men who had experienced a life-threatening, criminally motivated attack were interviewed about the event and their subsequent responses. The study was located within the qualitative research tradition allowing for the development of theory, and fox depth of description and interpretation. Semi-structured interviews were recorded and tnmscribdl w batim . Interview transcripts were subjected to a thematic content analysis by means of a computer-aided text interpretation. Frequency figures were calculated, but the emphasis of the analysis was in the area of descriptive and interpretive dimensions. Three central themes emerged as signi fi cant; those of Control, Disillusionment and Anger. Multiple facets of each theme are addressed, including centrally the interface between thematic dimensions and the social construction of masculinity. A meta-theoretical discourse analytic commentary is provided, addressing for example, the rob of the “hero” discourse in interviewee’s reports. In addition, the clinical implications of the data are explored. The study provides evidence of the inter-relationship between social and personal construction o f meaning in the aftermath of tramatization. It is suggested that in the context of victimization the social construction of masculinity is both more intractable and more permeable than might be supposed.
Thesis is submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, 1998
Keywords: Victims of crimes; Crime--South Africa; Post-traumatic stress disorder